2018
DOI: 10.1109/jxcdc.2018.2846202
|View full text |Cite
|
Sign up to set email alerts
|

Inversion Charge Boost and Transient Steep-Slope Induced by Free-Charge-Polarization Mismatch in a Ferroelectric-Metal–Oxide–Semiconductor Capacitor

Abstract: In this letter, the transient behavior of a ferroelectric (FE) metal-oxide-semiconductor (MOS) capacitor is theoretically investigated with a series resistor. It is shown that compared to a conventional high-k dielectric MOS capacitor, a significant inversion charge-boost can be achieved by a FE MOS capacitor due to a steep transient subthreshold swing (SS) driven by the free chargepolarization mismatch. It is also shown that the observation of steep transient SS significantly depends on the viscosity coeffici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…By subtracting V(c2) from V(u1), the voltage across CFE2 capacitor in MESO #2, V(cap2), can be obtained. Because of the transient negative capacitance effect in the FE [17], the absolute value of V(cap2) increases, decreases and again increases versus time during the FE switching. The voltage across the FE goes through the S-shaped polarization charge versus voltage curve of the ME material in this transient manner.…”
Section: Meso Invertermentioning
confidence: 99%
“…By subtracting V(c2) from V(u1), the voltage across CFE2 capacitor in MESO #2, V(cap2), can be obtained. Because of the transient negative capacitance effect in the FE [17], the absolute value of V(cap2) increases, decreases and again increases versus time during the FE switching. The voltage across the FE goes through the S-shaped polarization charge versus voltage curve of the ME material in this transient manner.…”
Section: Meso Invertermentioning
confidence: 99%
“…However, the transient operation of NCFETs is strongly dependent upon the viscosity factor (ρ) [25,26] which accounts for the polarization reversal in ferroelectrics. It offers the resistance in charge switching [27] and thus, restricts the use of NCFET for transient applications. According to the studies [25,28], the value of ρ must be below 0.1 Ω m for ferroelectric operation in MHz-GHz frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies [25,28], the value of ρ must be below 0.1 Ω m for ferroelectric operation in MHz-GHz frequency range. It has been reported that Hafnium based ferroelectric materials have the value of ρ in the range of 0.1 Ω m [27,29,30] which makes doped Hf ferroelectric materials suitable for high frequency applications. Therefore, taking into account the advantages of HCMOS and NCFETs, we have incorporated ferroelectric gate stack in p-GeOIFET (Ge-on-insulator FET) and n-SiGeOIFET (SiGe-oninsulator FET) and have implemented NCHCMOS (negative capacitance HCMOS) in the present paper.…”
Section: Introductionmentioning
confidence: 99%